Magnetization transfer ratio of peripheral nerve and skeletal muscle: correlation with demographic variables in healthy volunteers - Fösleitner, Olivia; Münch, Véronique; Godel, Tim; Preisner, Fabian; Bäumer, Philipp; Heiland, Sabine; Bendszus, Martin; Kronlage, Moritz (Clinical neuroradiology, 2022)
Purpose To assess the correlation of peripheral nerve and skeletal muscle magnetization transfer ratio (MTR) with demographic variables. - Methods In this study 59 healthy adults evenly distributed across 6 decades (mean age 50.5 years ±17.1, 29 women) underwent magnetization transfer imaging and high-resolution T2-weighted imaging of the sciatic nerve at 3 T. Mean sciatic nerve MTR as well as MTR of biceps femoris and vastus lateralis muscles were calculated based on manual segmentation on six representative slices. Correlations of MTR with age, body height, body weight, and body mass index (BMI) were expressed by Pearson coefﬁcients. Best predictors for nerve and muscle MTR were determined using a multiple linear regression model with forward variable selection and ﬁvefold cross-validation. - Results Sciatic nerve MTR showed signiﬁcant negative correlations with age (r = -0.47, p < 0.001), BMI (r = -0.44, p < 0.001), and body weight (r = -0.36, p = 0.006) but not with body height (p = 0.55). The multiple linear regression model determined age and BMI as best predictors for nerve MTR (R2 = 0.40). The MTR values were different between nerve and muscle tissue (p < 0.0001), but similar between muscles. Muscle MTR was associated with BMI (r = -0.46, p < 0.001 and r = -0.40, p = 0.002) and body weight (r = -0.36, p = 0.005 and r = -0.28, p = 0.035). The BMI was selected as best predictor for mean muscle MTR in the multiple linear regression model (R2 = 0.26). - Conclusion Peripheral nerve MTR decreases with higher age and BMI. Studies that assess peripheral nerve MTR should consider age and BMI effects. Skeletal muscle MTR is primarily associated with BMI but overall less dependent on demographic variables.